(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study analyzed therapeutic entrepreneurship and mental health condition in Nigeria. The study adopted quasi-experimental design and correlation design using systematic sampling and multi-stage cluster random sampling techniques. From the systematic population of 700 and sample size of 255 was determined using Slovin’s formula at 0.05 level of significance, whereas 231 were deem fit after processing, retriever, coding and cleansing. The instrument was validated by experiential entrepreneurs and reliability was conducted using Split half approach. Three research questions and three hypotheses were raised which was tested using regression analysis on the likelihood test was utilized via SPSS 25 version. From the findings, therapeutic entrepreneurship discipline, therapeutic entrepreneurship risk-culture, therapeutic entrepreneurship passion, therapeutic entrepreneurship competence, therapeutic entrepreneurship capital, therapeutic entrepreneurship spirit, therapeutic entrepreneurship charisma strongly rehabilitates mental health conditions among clusters of entrepreneurs. In conclusion, the apriori expectations were found to be positively rehabilitation tendency outcomes among the sustainable development goals, therapeutic entrepreneurship components and mental health condition. Hence, the regression model revealed that the alternate hypotheses were accepted, while the null hypotheses. Based on the findings and conclusion, this study contributes to the knowledge that the entrepreneurs journey, dream and vision could not be threaten by mental disorderliness with credible understanding and application of the components of therapeutic entrepreneurship as instruments. It could be recommended that therapeutic entrepreneurship spirit, charisma and passion of entrepreneur should be assessed with the model intervention to rehabilitates mental illness. Also, the therapeutic entrepreneurship capital should be seen from the symbolic, intellectual, social and cultural capital, which should stands as drive to boost egos of entrepreneur’s well-being and wellness in climax of disorderliness.